Penguatan Kapasitas Pokdarwis Nongkosawit melalui Penyuluhan Pariwisata: Pengabdian - R. Soelistijanto; Eko Heri Widiastuti; Agung Wibowo; Fathu Shodiqur Rohman; Anggun Istaurina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community engagement program aims to build the capacity of the Nongkosawit Tourism Awareness Group (Pokdarwis) through a tourism counseling initiative designed to strengthen the community’s understanding of local tourism potential, institutional roles, and sustainability principles in village-based tourism management. The program was implemented in Nongkosawit Village, Gunungpati District, Semarang City, involving youth groups and Pokdarwis members as the primary participants. The method adopted a counseling and empowerment approach grounded in Community-Based Tourism (CBT), beginning with a needs assessment followed by interactive lectures, focused group discussions, and technical training on tourism potential management and the functional strengthening of Pokdarwis. Data were collected through participatory observation, pre–post questionnaires, short interviews, and documentation, then analyzed qualitatively using descriptive techniques. The findings reveal significant improvements in participants’ understanding of Nongkosawit’s tourism assets, enhanced awareness of Pokdarwis’ strategic role in applying the Sapta Pesona principles, and increased insight into sustainable tourism practices. The counseling activities also stimulated new community-driven ideas related to tour package development, facility improvements, and the reinforcement of local tourism identity.